2014
DOI: 10.4028/www.scientific.net/amm.519-520.752
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Smart Tourism Service Mechanism Based on Context Awareness

Abstract: The traditional tourism services tend to use tourism resources as the center. They ignore individual characteristics and contextual information of the user side. The provided service is static, and doesnt meet the real needs of the users. A service mechanism based on context awareness is presented which consists of data, platform and services. It sets up data center based on users and gets context data according to rules .It uses the cloud computing technology to provide distributed processing, storage and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…e probability of good economic benefit of the project is 44.64%, so we can determine that the overall evaluation of the economic benefit of the smart city construction project in this city is good. In addition, we should 8 Complexity also see that the project's economic efficiency is good or general probability is 73.62%, greater than 50%; this conclusion indicates that, at this stage of the preproject evaluation, the smart city complex construction project of the financial profitability and project risk are acceptable to the project investment body. Respectively, draw radar chart for index combination weight analysis, as shown in Figure 5.…”
Section: Judgment Matrix Rowmentioning
confidence: 90%
See 1 more Smart Citation
“…e probability of good economic benefit of the project is 44.64%, so we can determine that the overall evaluation of the economic benefit of the smart city construction project in this city is good. In addition, we should 8 Complexity also see that the project's economic efficiency is good or general probability is 73.62%, greater than 50%; this conclusion indicates that, at this stage of the preproject evaluation, the smart city complex construction project of the financial profitability and project risk are acceptable to the project investment body. Respectively, draw radar chart for index combination weight analysis, as shown in Figure 5.…”
Section: Judgment Matrix Rowmentioning
confidence: 90%
“…Its development mainly depends on the continuous progress of science and technology. Now we live in an information society, and all kinds of living conditions are developing to a high level [8,9]. Smart city is now a collection of higher concepts.…”
Section: Planning and Construction Of Smart City In The Era Of Big Datamentioning
confidence: 99%
“…Kozuch et al (2009) demonstrated that location-aware applications outperform those with no location-aware capability by factor of 3-11 in the performance. Based on context awareness of data, platform and services, Feng et al (2014) presented a tourism service mechanism that dynamically adjusts the service mode based on the user context information and meets the demand for tourism services in conjunction with the individual user characteristics.…”
Section: Optimizing Big Data Platforms With Spatiotemporal Principlesmentioning
confidence: 99%
“…The authors of [142][143][144][145][146] proposed a context-aware recommendation system using smartphone sensors integrated with smart city applications and e-tourism, another recommendation system based on tourist context [147,148]. The authors of [49,73,149,150] proposed a system of travel recommendations that mines appropriate locations, context, user preferences [151][152][153] users' reviews [154], sentiments analysis [1], and users' physical and psychological functionality levels [155].…”
Section: Traveling and Poimentioning
confidence: 99%